The Protective Effect of Trichilia catigua A. Juss. on DEHP-Induced Reproductive System Damage in Male Mice - Chang, Xinyue; Dong, Mingran; Mi, Xiao; Hu, Meigeng; Lu, Juan; Chen, Xi (Frontiers in Pharmacology, 2022)
The present study aimed to explore the protective effect and molecular mechanisms of Trichilia catigua A. Juss. extract (TCE) against di(2-ethylhexyl) phthalate (DEHP)-induced damage to the reproductive system of mice. Acute toxicity tests revealed that the maximum tolerated dose (MTD) in mice was up to 2.7 g•kg–1. After induction with DEHP, TCE (L-TCE, M-TCE, H-TCE) was orally administered to mice for 28 days. Differences in indicators among groups showed that TCE significantly improved the anogenital distance and the organ indexes of the epididymides and testes. It also significantly reduced varicocele and interstitial cell lesions compared to the model group. H-TCE reduced the sperm abnormality rate, increased the levels of sex hormones, Na+K+ and Mg2+, Ca2+-ATPase enzyme activity, antioxidant enzyme vitality, coupled with a significant decrease in LH and MDA contents. The levels of testicular marker enzymes ACP and LDH were significantly augmented by both M-TCE and H-TCE. Further studies claimed that DEHP induction reduced the mRNA expression levels of Nrf2, SOD2, SOD3, CDC25C CDK1, CYP11A1, 3β-HSD, 5ɑ-R, AR, SF1, and CYP17A1, increased the level of Keap1, while TCE reversed the expression levels of these genes. Meanwhile, IHC results demonstrated a significant change in the expression activity of the relevant proteins compared to the control group. The results suggest that M-TCE and H-TCE enabled the recovery of DEHP-induced reproductive system damage in male mice by improving testicular histopathology, repairing testicular function, and reducing oxidative stress damage. The oxidation-related Keap1-Nrf2 pathway, SODs enzyme, the cell cycle control-related CDC25C-CDK1 pathway, and the steroidogenic-related pathway may contribute to this protective effects of TCE.